Accurate retrieval of ionization times by means of the phase-of-the-phase spectroscopy, and its limits - Wuerzler, D.; Skruszewicz, S.; Sayler, A. M.; Zille, D.; Moeller, M.; Wustelt, P.; Zhang, Yinyu; Tiggesbaeumker, J.; Paulus, Gerhard G. (Physical Review A, 2020)
By applying recently introduced, phase-of-the-phase spectroscopy [S. Skruszewicz et al., Phys. Rev. Lett. 115, 043001 (2015)PRLTAO0031-900710.1103/PhysRevLett.115.043001], we analyze the phase-dependent photoelectron signal from Xe ionized in intense, parallel, two-color (1800 nm and 900 nm) laser fields. With such a field configuration, tuning of the relative phase between the ionizing, ω, and the perturbative, 2ω, field results in a modulation of the ionization rate, as well as modifications of the trajectories of electrons propagating in the laser-dressed continuum. Based on a semiclassical model, we confirm that phase dependencies, due to the perturbation of the ionization rate, encode the ionization times of the electrons. Here, using the fork structure, a well-known feature originating from well-defined dynamics allows us to distinguish between electrons ionized within distinct time windows. However, due to the simultaneous perturbation of the electron trajectories, the assignment of the ionization times can be distorted by up to 80 as, i.e., a 10 phase shift, which is independent of the degree of the perturbation.
CRIS-Team Scopus Importer:2023-04-20